Search for Higgs boson pair production in the b ¯bb¯b final state from pp collisions at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
A search for Higgs boson pair production pp → hh is performed with 19.5 fb−1 of proton–proton collision data at √s = 8TeV, which were recorded by the ATLAS detector at the Large Hadron Collider in 2012. The decay products of each Higgs boson are reconstructed as a high momentum b¯b system with either a pair of small-radius jets or a single large-radius jet, the latter exploiting jet substructure techniques and associated b-tagged track-jets. No evidence for resonant or non-resonant Higgs boson pair production is observed. The data are interpreted in the context of the Randall–Sundrum model with a warped extra dimension as well as the two-Higgs-doublet model. An upper limit on the cross-section for pp → G∗ KK → hh → b ¯ bb¯b of 3.2 (2.3) fb is set for a Kaluza–Klein graviton G∗ KK mass of 1.0 (1.5)TeV, at the 95 % confidence level. The search for non-resonant Standard Model hh production sets an observed 95 % confidence level upper limit on the production cross-section σ(pp → hh → b ¯ bb¯b ) of 202 fb, compared to a Standard Model prediction of σ(pp → hh → b ¯ bb¯b) = 3.6 ± 0.5fb.